Epidemiology of ovarian cancer in Assiut Governorate, Egypt - Gharib, Mahmoud Ahmed; El-Shoeiby, Mahmoud Hussein; Metwally, Nagy Mohammed; Rashid, Yostina Maher (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this study is to assess ovarian cancer epidemiology and detect its prognostic factors in Assuit, Egypt. Methods: This retrospective study was performed between January 2010 and December 2015, on all cases attending to Obstetrics and Gynecology Outpatient Clinic in all central hospitals in Assiut. 378 females (≥40 years old) came to Obstetrics and Gynecology Outpatient Clinic from January 2010 to December 2015. Inclusion criteria: All females (≥40 years old), history of current acute or chronic pelvic pain, mass; fixed, hard consistency, history of previous similar condition. Results: Mean age for whole ovarian cancer cases in this study was 56.44±10.08 (range, 40-85). Nulliparity was found in one case (0.3%), while multiparity was found in 252 cases (66.7%). Grand multiparity was found in 113 cases (29.9%). Twelve cases (3.2%) were virgin. Vaginal ultrasound can find all ovarian cancer cases. Regarding the serum levels of the tumor biomarker, CA-125, the average level of CA-125 is 300-1000 U/ml with 34.9% of cases had readings below to 300-1000 U/ml and 6.1% of cases had readings above to this average level. Regarding treatment, treatment combining surgery with chemotherapy was the main line of management in present study (46.3%). About 33.3% of cases underwent surgery, while only 18.3% took the chance of chemotherapy. Eight cases (2.1%) had no treatment. Conclusions: Epithelial ovarian cancer is a lethal disease. The age incidence of ovarian cancer in present patients is ten years younger than what is re¬ported in US SEER data and other Western countries. CA-125 level and ultrasonography are increasing the rate of suspicious for diagnosis of malignant tumors.